2002
DOI: 10.1139/x02-059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic N fertilization on foliar membranes, cold tolerance, and carbon storage in montane red spruce

Abstract: We evaluated the influence of protracted low-level nitrogen (N) fertilization on foliar membrane-associated calcium (mCa), sugar and starch concentrations, membrane stability, winter cold tolerance, and freezing injury of red spruce (Picea rubens Sarg.) trees growing in six experimental plots on Mount Ascutney, Vermont. For 12 consecutive years before this evaluation, each plot received one of three treatments: 0, 15.7, or 31.4 kg N·ha–1·year–1 supplied as NH4Cl. In comparison with trees from control plots, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 53 publications
1
52
0
Order By: Relevance
“…Th is eff ect is documented for boreal forest trees (e.g., Aronsson 1980, Balsberg-Påhlsson 1992, Kallio et al 1985, Schaberg et al 2002, for their common understory ericaceous species (e.g., Strengbom et al 2002Strengbom et al , 2003, and for bogs (e.g., Wiedermann et al 2007). At higher deposition levels, as N is no longer completely taken up by vegetation or immobilized in soils, N saturation and leaching may occur (Lamontagne 1998;Lamontagne andSchiff 1999, 2000;Tamm et al 1999).…”
Section: Ecosystem Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Th is eff ect is documented for boreal forest trees (e.g., Aronsson 1980, Balsberg-Påhlsson 1992, Kallio et al 1985, Schaberg et al 2002, for their common understory ericaceous species (e.g., Strengbom et al 2002Strengbom et al , 2003, and for bogs (e.g., Wiedermann et al 2007). At higher deposition levels, as N is no longer completely taken up by vegetation or immobilized in soils, N saturation and leaching may occur (Lamontagne 1998;Lamontagne andSchiff 1999, 2000;Tamm et al 1999).…”
Section: Ecosystem Responsesmentioning
confidence: 99%
“…As a consequence, whortleberry density decreased, and wavy hairgrass cover increased (Strengbom et al 2002). In addition, shoots of whortleberry were signifi cantly more damaged by moth larvae such as the rusty tussock moth (Orgyia antique) after addition of 12.5 kg N ha -1 yr -1 in the fi rst year of treatment (Nordin et al 1998 ) showed diminished cold tolerance, greater electrolyte leakage, and increased susceptibility to frost damage (Schaberg et al 2002). Nutrient imbalances created by N and sulfur (S) fertilization and low potassium (K), phosphorus (P), and magnesium (Mg) status in southern Sweden and Denmark have been shown to increase the risk for development of cold temperature-related bark lesions in beech (Fagus spp.…”
Section: Forests and Woodlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have showed that the values of photosynthesis parameters significantly increase in Cryptomeria japonica and hybrid poplar seedlings according to the degree of N deposition, while they decrease when the amount of N exceeds the critical point (Nakaji et al 2001;Cooke et al 2005). On the other hand, other studies have found that there is no relationship between N deposition and photosynthesis in spruce (Schaberg et al 2002). Our results showed that N addition significantly decreased P max and L SP and significantly increased L CP in the low-elevation population.…”
Section: Effects Of N Addition On Growth and Physiological Variables mentioning
confidence: 99%
“…Without an adequate supply of base cations, trees are susceptible to toxicity from Al in excessively acidic environments and from nutritional defi ciency of base cations. Consequences of base cation depletion include reduced cold tolerance and increased winter injury (DeHayes et al 1999, Schaberg et al 2000, crown dieback (Wilmot et al 1995), increased susceptibility to pest and disease (McLaughlin and Wimmer 1999), reduced regeneration, reduced growth and increased mortality (Schaberg et al 2002), and species composition changes.…”
Section: Base Cation Depletionmentioning
confidence: 99%